Metabolomic Evenness Underlies Intraspecific Differences Among Lineages of a Wetland Grass - Salgado, Ana L; Glassmire, Andrea E; Sedio, Brian E; Diaz, Rodrigo; Stout, Michael J; Čuda, Jan; Pyšek, Petr; Meyerson, Laura A; Cronin, James T (Journal of chemical ecology, 2023)
The metabolome represents an important functional trait likely important to plant invasion success, but we have a limited understanding of whether the entire metabolome or targeted groups of compounds confer an advantage to invasive as compared to native taxa. We conducted a lipidomic and metabolomic analysis of the cosmopolitan wetland grass Phragmites australis. We classified features into metabolic pathways, subclasses, and classes. Subsequently, we used Random Forests to identify informative features to differentiate five phylogeographic and ecologically distinct lineages: European native, North American invasive, North American native, Gulf, and Delta. We found that lineages had unique phytochemical fingerprints, although there was overlap between the North American invasive and North American native lineages. Furthermore, we found that divergence in phytochemical diversity was driven by compound evenness rather than metabolite richness. Interestingly, the North American invasive lineage had greater chemical evenness than the Delta and Gulf lineages but lower evenness than the North American native lineage. Our results suggest that metabolomic evenness may represent a critical functional trait within a plant species. Its role in invasion success, resistance to herbivory, and large-scale die-off events common to this and other plant species remain to be investigated.
Keywords: fenotyp; Ecological Omics; Phytochemistry; Invasive Plant Species; Liquid Chromatography–Mass Spectrometry (LC–MS); lipnicovité; Plants; fytonutrienty; Phytochemicals; Invasion Ecology; Phenotype; Common Reed; rostliny; mokřady; Wetlands; Poaceae